Systematic Literature Review: Does Problem Based Learning Model Effectively Improve Mathematical Reasoning Ability? - Gisela Anastacia Rosalind; Shelly Morin; Veni Saputri (Didaktika: Jurnal Kependidikan, 2024)
Mathematical reasoning ability refers to a person's ability to use logic and critical thinking in a mathematical context. However, in Indonesia, students' mathematical reasoning abilities from elementary school to tertiary college. Therefore, a more vary learning model is needed, such as the Problem Based Learning (PBL) model, to improve students' mathematical reasoning abilities. PBL focuses on solving real and relevant problems collaboratively. The research method used in this article is Systematic Literature Review (SLR). There are 35 articles that will be explained and are in accordance with this research from 2017-2023. The findings indicate that PBL effectively enhances mathematical reasoning abilities across various educational levels and covers a range of mathematical topics. Notably, PBL is more beneficial for students with medium and low academic abilities compared to those with high abilities. Additionally, some studies suggest that PBL may positively impact students' metacognitive skills, though further research is needed to identify other influencing factors. This study recommends additional research to explore these factors and to experiment with PBL models using different open materials.